Sequence dependent lipid-mediated effects modulate the dimerization of ErbB2 and its associative mutants - Prasanna, Xavier; Praveen, P. J.; Sengupta, Durba (Physical Chemistry Chemical Physics, 2013)
The association of transmembrane helices is an important event in several biological processes, but the factors governing association, especially the non-specific environmental effects, have still not been elucidated. Here, we use coarse-grain molecular dynamics simulations to study the association of ErbB2 transmembrane helices and three ``oncogenic mutants.'' Self-assembly simulations and the dimerization free-energy profiles confirm an energetically-favorable dimerized state for both the wildtype and the mutants. The dissociation free energy of all three mutants is calculated to be larger than the wildtype peptide. Along with favourable protein-protein interactions, non-specific environmental effects are observed to contribute to the association. In particular, local bilayer thinning along with membrane perturbations are seen around the mutants. The membrane perturbations are reduced upon helix association, suggesting that lipid chain packing is an important driving force for helix dimerization. Our results highlight the importance of both specific as well as non-specific driving forces in the association of transmembrane helices.

Cholesterol modulates the dimer interface of the beta(2)-adrenergic receptor via cholesterol occupancy sites - Prasanna, Xavier; Chattopadhyay, Amitabha; Sengupta, Durba (Biophysical Journal, 2014)
The beta(2)-adrenergic receptor is an important member of the G-protein-coupled receptor (GPCR) superfamily, whose stability and function are modulated by membrane cholesterol. The recent high-resolution crystal structure of the beta(2)-adrenergic receptor revealed the presence of possible cholesterol-binding sites in the receptor. However, the functional relevance of cholesterol binding to the receptor remains unexplored. We used MARTINI coarse-grained molecular-dynamics simulations to explore dimerization of the beta(2)-adrenergic receptor in lipid bilayers containing cholesterol. A novel (to our knowledge) aspect of our results is that receptor dimerization is modulated by membrane cholesterol. We show that cholesterol binds to transmembrane helix IV, and cholesterol occupancy at this site restricts its involvement at the dimer interface. With increasing cholesterol concentration, an increased presence of transmembrane helices I and II, but a reduced presence of transmembrane helix IV, is observed at the dimer interface. To our knowledge, this study is one of the first to explore the correlation between cholesterol occupancy and GPCR organization. Our results indicate that dimer plasticity is relevant not just as an organizational principle but also as a subtle regulatory principle for GPCR function. We believe these results constitute an important step toward designing better drugs for GPCR dimer targets.

Differential dynamics of the serotonin(1A) receptor in membrane bilayers of varying cholesterol content revealed by all atom molecular dynamics simulation - Patra, Swarna M.; Chakraborty, Sudip; Shahane, Ganesh; Prasanna, Xavier; Sengupta, Durba; Maiti, Prabal K.; Chattopadhyay, Amitabha (Molecular Membrane Biology, 2015)
The serotonin(1A) receptor belongs to the superfamily of G protein-coupled receptors (GPCRs) and is a potential drug target in neuropsychiatric disorders. The receptor has been shown to require membrane cholesterol for its organization, dynamics and function. Although recent work suggests a close interaction of cholesterol with the receptor, the structural integrity of the serotonin(1A) receptor in the presence of cholesterol has not been explored. In this work, we have carried out all atom molecular dynamics simulations, totaling to 3s, to analyze the effect of cholesterol on the structure and dynamics of the serotonin(1A) receptor. Our results show that the presence of physiologically relevant concentration of membrane cholesterol alters conformational dynamics of the serotonin(1A) receptor and, on an average lowers conformational fluctuations. Our results show that, in general, transmembrane helix VII is most affected by the absence of membrane cholesterol. These results are in overall agreement with experimental data showing enhancement of GPCR stability in the presence of membrane cholesterol. Our results constitute a molecular level understanding of GPCR-cholesterol interaction, and represent an important step in our overall understanding of GPCR function in health and disease.
Keywords: GPCR; Membrane cholesterol; molecular dynamics simulation; serotonin(1A) receptor

Effect of lipid bilayer composition on membrane protein association - Pawar, Aiswarya B.; Prasanna, Xavier; Sengupta, Durba (Advances in Planar Lipid Bilayers and Liposomes, 2015)
Diverse cellular functions are supported by membrane protein assemblies associated with the cell membrane. Although considered to be protein-mediated, membrane components are now being recognized as critical in modulating and sometime dictating function. This chapter discusses the effect of the lipid bilayer, in particular its composition on membrane protein organization. Computational methods have been successful in quantifying transmembrane protein association and general features of dimerization profiles are explored. Understanding the molecular basis of the interactions has lead to the recognition of the lipophobic effects. These nonspecific effects include those that arise from membrane perturbations and lipid chain packing and have been shown to modulate the energetics as well as the structural characteristics of membrane protein dimerization. In addition, specific interactions arising from direct protein–lipid interactions and protein–cholesterol interactions have been suggested to influence membrane protein association. We summarize here a few examples highlighting the role of the lipid bilayer on membrane protein organization.

Role of lipid-mediated effects in beta(2)-adrenergic receptor dimerization - Prasanna, Xavier; Chattopadhyay, Amitabha; Sengupta, Durba (biochemical roles of eukaryotic cell surface macromolecules, 2015)

Cholesterol-dependent conformational plasticity in GPCR dimers - Prasanna, Xavier; Sengupta, Durba; Chattopadhyay, Amitabha (Scientific Reports, 2016)
The organization and function of the serotonin1A receptor, an important member of the GPCR family, have been shown to be cholesterol-dependent, although the molecular mechanism is not clear. We performed a comprehensive structural and dynamic analysis of dimerization of the serotonin1A receptor by coarse-grain molecular dynamics simulations totaling 3.6 ms to explore the molecular details of its cholesterol-dependent association. A major finding is that the plasticity and flexibility of the receptor dimers increase with increased cholesterol concentration. In particular, a dimer interface formed by transmembrane helices I-I was found to be sensitive to cholesterol. The modulation of dimer interface appears to arise from a combination of direct cholesterol occupancy and indirect membrane effects. Interestingly, the presence of cholesterol at the dimer interface is correlated with increased dimer plasticity and flexibility. These results represent an important step in characterizing the molecular interactions in GPCR organization with potential relevance to therapeutic interventions.

Conformational dynamics of GPCR dimers is dependent on membrane cholesterol - Sengupta, Durba; Prasanna, Xavier; Chattopadhyay, Amitabha (Biophysical Journal, 2016)

Protein-dependent membrane interaction of a partially disordered protein complex with oleic acid : Implications for cancer lipidomics - Chaudhuri, Arunima; Prasanna, Xavier; Agiru, Priyanka; Chakraborty, Hirak; Rydstrom, Anna; Ho, James C. S.; Svanborg, Catharina; Sengupta, Durba; Chattopadhyay, Amitabha (Scientific Reports, 2016)
Bovine α-lactalbumin (BLA) forms cytotoxic complexes with oleic acid (OA) that perturbs tumor cell membranes, but molecular determinants of these membrane-interactions remain poorly understood. Here, we aim to obtain molecular insights into the interaction of BLA/BLA-OA complex with model membranes. We characterized the folding state of BLA-OA complex using tryptophan fluorescence and resolved residue-specific interactions of BLA with OA using molecular dynamics simulation. We integrated membrane-binding data using a voltage-sensitive probe and molecular dynamics (MD) to demonstrate the preferential interaction of the BLA-OA complex with negatively charged membranes. We identified amino acid residues of BLA and BLA-OA complex as determinants of these membrane interactions using MD, functionally corroborated by uptake of the corresponding α-LA peptides across tumor cell membranes. The results suggest that the α-LA component of these cytotoxic complexes confers specificity for tumor cell membranes through protein interactions that are maintained even in the lipid complex, in the presence of OA.

Chapter 5: Experimental and computational approaches to study membranes and lipid-protein interactions - Sengupta, Durba; Kumar, G. Aditya; Prasanna, Xavier; Chattopadhyay, A. (Computational biophysics of membrane proteins, 2017)
Biological membranes are complex two-dimensional, non-covalent assemblies of a diverse variety of lipids and proteins. A hallmark of membrane organization is varying degrees of spatiotemporal heterogeneity spanning a wide range. Membrane proteins are implicated in a wide variety of cellular functions, and comprise ∼30% of the human proteome and ∼50% of the current drug targets. Their interactions with membrane lipids are recognized as crucial elements in their function. In this article, we provide an overview of experimental and theoretical approaches to analyze membrane organization, dynamics, and lipid-protein interactions. In this context, we highlight the wide range of time scales that membrane events span, and approaches that are suitable for a given time scale. We discuss representative fluorescence-based approaches (FRET and FRAP) that help to address questions on lipid-protein and protein-cytoskeleton interactions in membranes. In a complimentary fashion, we discuss computational methods, atomistic and coarse-grain, that are required to address a given membrane problem at an appropriate scale. We believe that the synthesis of knowledge gained from experimental and computational approaches will enable us to probe membrane organization, dynamics, and interactions at increasing spatiotemporal resolution, thereby providing a robust model for the membrane in health and disease.

Estimating the lipophobic contributions in model membranes - Dubey, Vikas; Prasanna, Xavier; Sengupta, Durba (Journal of Physical Chemistry B, 2017)
The insertion and association of membrane proteins is critical in several cellular processes. These processes were thought to be protein-driven, but increasing evidence points toward an important role of the lipid bilayer. The lipid-mediated contribution has been shown to be important in the association of membrane peptides, but the corresponding ``lipophobic'' component has not been directly estimated. Here, we calculate the free energy of insertion for transmembrane peptides and estimate the lipophobic component from the cost of cavity formation. The free-energy calculations were performed using the coarse-grain Martini force field, which has been successful in predicting membrane protein interactions. As expected, the charged moieties have the least favorable free energy of insertion and the highest cost of cavity formation. A length dependence was observed in polyalanine peptides with the lipid-mediated component increasing nonlinearly with peptide length. Membrane fluidity was tested by varying the temperature, and opposing effects were observed for short and long peptides. The dependence of the lipid-mediated effects on peptide length and temperature was not uniform and gives valuable insight into the anisotropic nature of the membrane. The results are an important step in estimating membrane effects in protein insertion and association.

Exploring GPCR lipid interactions by molecular dynamics simulations: excitements, challenges, and the way forward - Sengupta, Durba; Prasanna, Xavier; Mohole, Madhura; Chattopadhyay, Amitabha (Journal of Physical Chemistry B, 2018)
Gprotein-coupled receptors (GPCRs) are seven transmembrane receptors that mediate a large number of cellular responses and are important drug targets. One of the current challenges in GPCR biology is to analyze the molecular signatures of receptor-lipid interactions and their subsequent effects on GPCR structure, organization, and function. Molecular dynamics simulation studies have been successful in predicting molecular determinants of receptor-lipid interactions. In particular, predicted cholesterol interaction sites appear to correspond well with experimentally determined binding sites and estimated time scales of association. In spite of several success stories, the methodologies in molecular dynamics simulations are still emerging. In this Feature Article, we provide a comprehensive overview of coarse-grain and atomistic molecular dynamics simulations of GPCR-lipid interaction in the context of experimental observations. In addition, we discuss the effect of secondary and tertiary structural constraints in coarse-grain simulations in the context of functional dynamics and structural plasticity of GPCRs. We envision that this comprehensive overview will help resolve differences in computational studies and provide a way forward.

Role of cholesterol-mediated effects in GPCR heterodimers - Prasanna, Xavier; Mohole, Madhura; Chattopadhyay, Amitabha; Sengupta, Durba (Chemistry and Physics of Lipids, 2020)
G protein-coupled receptors (GPCRs) are transmembrane receptors that mediate a large number of cellular responses. The organization of GPCRs into dimers and higher-order oligomers is known to allow a larger repertoire of downstream signaling events. In this context, a crosstalk between the adenosine and dopamine receptors has been reported, indicating the presence of heterodimers that are functionally relevant. In this paper, we explored the effect of membrane cholesterol on the adenosine(2A) (A(2A)) and dopamine D-3 (D-3) receptors using coarse-grain molecular dynamics simulations. We analyzed cholesterol interaction sites on the A(2A) receptor and were able to reproduce the sites indicated by crystallography and previous atomistic simulations. We predict novel cholesterol interaction sites on the D-3 receptor that could be important in the reported cholesterol sensitivity in receptor function. Further, we analyzed the formation of heterodimers between the two receptors. Our results suggest that membrane cholesterol modulates the relative population of several co-existing heterodimer conformations. Both direct receptor-cholesterol interaction and indirect membrane effects contribute toward the modulation of heterodimer conformations. These results constitute one of the first examples of modulation of GPCR hetero-dimerization by membrane cholesterol, and could prove to be useful in designing better therapeutic strategies.
Keywords: Adenosine(2A) receptor; Cholesterol; Dopamine D-3 receptor; G protein-coupled receptors; Heterodimer; MARTINI coarse-grain simulation